Prevalence of pre-eclampsia in women in the Middle East: a scoping review - Hegazy, Ayatullah; Eid, Farida Abdelrehim; Ennab, Farah; Sverrisdóttir, Yrsa Bergmann; Atiomo, William; Azar, Aida Joseph (Frontiers in Public Health, 2024)
Hypertensive disorders of pregnancy are the second most common cause of maternal deaths worldwide. Metabolic syndrome is recognized as one of the risk factors for pre-eclampsia. A recent study revealed a high prevalence of metabolic syndrome in the United Arab Emirates (UAE), particularly amongst Emirati women compared with global estimates. This finding raises the possibility that the prevalence of pre-eclampsia in the region may also be higher as research is increasingly demonstrating an association between pre-eclampsia and metabolic syndrome. We therefore conducted this scoping review of the literature to investigate the nature and extent of studies evaluating the prevalence of pre-eclampsia within the Middle East region to enable subsequent comparison of these findings with the global burden of pre-eclampsia, objectively identify gaps in the literature and inform the design of future studies to address these gaps. PubMed and Scopus were used to extract studies published over the last 20 years (2003–2023). The search terms used included (“Pre-eclampsia” AND “Prevalence”) OR (“Hypertension in pregnancy” AND “Prevalence”) OR (“Pregnancy” AND “Pre-eclampsia”) OR (“Pre-eclampsia” AND “Epidemiology”). We limited our studies to those from the Middle East (ME). A total of 556 relevant articles were identified following which 11 were shortlisted for review. There were four studies from Iran, two from Saudi Arabia, two from Qatar, one from Jordan, and one from Bahrain. The remaining study included 29 countries from Africa, Asia, Latin America, and the Middle East of which data from Jordan, Lebanon, the Occupied Palestinian Territory, and Qatar were included. There were four retrospective, two cross-sectional, and two cohort studies, one prospective study, one meta-analysis, and one descriptive-analytical study. The prevalence of pre-eclampsia in the studies ranged from 0.17 to 5%. We did not find any study investigating the prevalence of pre-eclampsia in the United Arab Emirates. Based on our findings, we conclude that there is a significant scarcity of research in this area, especially within the Middle East, and notably an absence of studies specifically pertaining to the UAE. Consequently, we assert that there is a pressing requirement for additional research to evaluate the prevalence of pre-eclampsia in the region.